1976
DOI: 10.1126/science.1251212
|View full text |Cite
|
Sign up to set email alerts
|

Selenium in Fly Ash

Abstract: Selenium, at concentrations exceeding 200 parts per million (ppm) (dry weight), has been found in white sweet clover voluntarily growing on beds of fly ash in central New York State. Guinea pigs fed such clover concentrated selenium in their tissues. The contents of the honey stomachs of bees foraging on this seleniferous clover contained negligible selenium. Mature vegetables cultured on 10 percent (by weight) fly ash-amended soil absorbed up to 1 ppm of selenium. Fly ashes from 21 states contained total sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

1977
1977
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(41 citation statements)
references
References 5 publications
1
39
1
Order By: Relevance
“…The addition of fly ash to soil or aquatic habitats can result in increased Se contents in the plants, animals, and other organisms indigenous to these environments. Gutenmann et al (1976) reported that cabbage plants grown on soils containing 10% fly ash absorbed Se (up to 3.7 ppm) in direct proportion to the Se content of the fly ash. Also, sweetclover plants growing directly on fly ash disposal piles contained over 200 ppm Se.…”
Section: Mobilization Of Seleniummentioning
confidence: 99%
“…The addition of fly ash to soil or aquatic habitats can result in increased Se contents in the plants, animals, and other organisms indigenous to these environments. Gutenmann et al (1976) reported that cabbage plants grown on soils containing 10% fly ash absorbed Se (up to 3.7 ppm) in direct proportion to the Se content of the fly ash. Also, sweetclover plants growing directly on fly ash disposal piles contained over 200 ppm Se.…”
Section: Mobilization Of Seleniummentioning
confidence: 99%
“…Higher levels of molybdenum can produce a disorder called "molybdenosis,,' or molybdenum-induced copper deficiency in animals. Results from field and 1 greenhouse studies with fly ash indicate that selenium concentrations in some crop species approached the foregoing critical levels (Furr et al, 1977;Straughan et al, 1979) and in one particular circumstance exceeded these levels (Gutenmann et al, 1976). Tests with small animals showed elevated selenium and molybdenum concentrations in their tissues and organs when they were fed plant rations grown on fly-ash-;…”
Section: F L Y Ash I N S O I L P E R C E N T ( P E R C E N T )mentioning
confidence: 95%
“…Epidemiological studies in children and studies in animals have shown that the incidence of caries is increased by selenium (126). In view of the potentially hazardous effects of excess selenium demonstrated in animals and the reports which indicate release of selenium into the environment in the process of coal combustion (127)(128)(129) the proposed studies of selenium metabolism in man are highly relevant. Commission's Contribution $56,365 In addition to above: VA contribution $10,000…”
Section: Scientific Backgroundmentioning
confidence: 99%